The sense of wonder - Carson, Rachel, 1907-1964 (Harper & Row, 1965)
The Sense of Wonder relates Carson's intimate account of adventures with her young nephew, in their walks along the sea coast and through forests and fields, observing wildlife, strange plants, moonlight, and storm clouds. It is a guide to capturing the simple power of discovery that Carson viewed as essential to life.